Tingkat Keterampilan Pukulan Backhand Pada Peserta Ekstrakulikuler Tenis Meja di SMPN Se-Kecamatan Lemahabang Karawang - Lisnawati, Nur Aini; Gani , Ruslan Abdul; Yuda , Aria Kusuma (Universitas Hamzanwadi, 2024)
This research uses a quantitative descriptive approach. The purpose of this study was to determine the ability of backhand shots of students who take part in table tennis extracurricular activities. The research subjects were all students who participated in table tennis extracurricular activities, there were 2 middle schools with a total of 60 male students and 24 female students. The sample used was total sampling. Data collection using tests, with the instrument used in the form of a back board test. The data analysis technique uses descriptive analysis in the form of %. The results showed 12 male students 20.0% declared very less, 16 students 26.7% declared less, 22 students 36.7% declared moderate, 10 students 16.7% declared good, and 0 students 0% declared very good. The highest frequency is 36.7%, which is in the moderate category. It is concluded that the forehand shot ability of male students who take part in extracurricular table tennis is in the moderate category. 16 female students 66.7% declared very less, 0 students 0% declared less, 4 students 16.7% declared moderate, 2 students 8.3% declared good, and 2 students 8.3% declared very good. The highest frequency is 66.7%, which is in the very poor category. It is concluded that the forehand shot ability of female students who take part in table tennis extracurricular activities is in the very poor category.